Insights into the molecular characteristics of embryonic cranial neural crest cells and their derived mesenchymal cell pools - Hengxing Ba; Qianqian Guo; Yudong Shang; Pengfei Hu; Chao Ma; Jiping Li; Dawn Elizabeth Coates; Chunyi Li (Communications Biology)
Abstract Neural crest cells (NCCs) are central to vertebrate embryonic development, giving rise to diverse cell types with unique migratory and differentiation capacities. This study examines the molecular characteristics of cranial neural crest cell (CNCC)-derived mesenchymal cells, specifically those from teeth which in deer show continuous but limited growth, and antlers, which exhibit remarkable regenerative capabilities. Here, through single-cell RNA sequencing analysis, we uncover shared gene expression profiles between adult antlerogenic and dental mesenchymal cells, indicating common developmental pathways. We identify a striking resemblance in transcriptomic features between antlerogenic progenitor cells and dental pulp mesenchymal cells. Comparative analysis of CNCC-derived and non-CNCC-derived mesenchymal cell pools across species reveals core signature genes associated with CNCCs and their derivatives, delineating essential connections between CNCCs and CNCC-derived adult mesenchymal pools. Furthermore, whole-genome DNA methylation analysis unveils hypomethylation of CNCC derivate signature genes in regenerative antlerogenic periosteum, implying a role in maintaining multipotency. These findings offer crucial insights into the developmental biology and regenerative potential of CNCC-derived mesenchymal cells, laying a foundation for innovative therapeutic strategies in tissue regeneration.